Hydrological modelling for urban drainage capacity assessment in a rapidly urbanizing commercial corridor: A case study from Pontianak, Indonesia - Ikhwan Arief Purnama; Imanuel Kemenangenta Perangin Angin; Randy Setiawan (CV. FOUNDAE, 2026)
Background: Rapid urbanization has increased impervious surfaces in commercial areas, leading to higher surface runoff and reducing the performance of existing urban drainage systems during intense rainfall events. As a result, many drainage networks are no longer capable of conveying design runoff, increasing the risk of urban inundation and disrupting transportation and commercial activities. Aims: This study aimed to assess the hydraulic capacity of the existing drainage system along Prof. M. Yamin Road, Pontianak, Indonesia, and to develop an optimal drainage design based on hydrological modelling. Methods: A quantitative approach was employed using field measurements and annual maximum rainfall data collected over a ten-year period (2015–2024). Design rainfall was estimated using the Gumbel frequency distribution, rainfall intensity was calculated using the Mononobe equation, and peak runoff was determined through the Rational Method. The hydraulic performance of the existing drainage channels was subsequently evaluated using Manning's equation by comparing the channel capacity with the estimated design discharge. Results: The estimated design rainfall was 255.13 mm, generating a rainfall intensity of 138.75 mm h⁻¹ and a peak runoff discharge of 1.169 m³ s⁻¹. The drainage channel toward Sutan Syahrir exhibited a capacity of 2.85 m³ s⁻¹ and was hydraulically adequate, whereas the channel toward Kota Baru provided only 0.375 m³ s⁻¹, indicating insufficient capacity to accommodate the design discharge. Conclusion: The integration of hydrological modelling and hydraulic analysis provides a reliable framework for assessing urban drainage capacity and supports evidence-based planning for effective stormwater management in rapidly urbanizing commercial corridors.